The Problem of Preservation of Personal Space in the Global Infromation Society - Galant, Daria; Kovalev, Eugene (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article deals with the problem of awareness and preservation of one’s own human space in the global information world. The authors suggest various ways of improving personal space, deliberating problems in the field of its protection as self-identification of an individual.
Keywords: ICT; White Emotion Theory; School of Philosophy; development; art; nature; space of life; coaching; education